143 User Characteristics of Unique Men's Health Website. Issue 1 (1st April 2022) - Alom, M; Collins, S; Nelson, K; Carlson, S; Tentis, E; Helo, S; Ziegelmann, M; Trost, L; Kohler, T
ABSTRACT: Introduction: Covid-19 has helped drive all forms of medicine away from traditional brick and mortar medical interactions. Given the availability of online services to obtain treatments for ED, we developed a website to facilitate patient education, triage and men's health appointment scheduling. Objective: We sought to assess characteristics of men who utilized a novel website to treat their ED. Methods: We report on 50 patients who ultimately booked and attended appointments (video or in person) for erectile dysfunction. Patients found our website through our institution's main informational ED pages or through youtube links from our men's health video playlist library. Patients create an institutional account and are then asked a series of MD created questions designed to streamline patient triage and complete the majority of chart documentation ahead of the appointment. Patients are then sent videos relevant to their condition and future appointment options. Results: 2300 users investigated the ED portion of the website with 1.8% of patients ultimately following through with an appointment. 13% of patients who explored the ED portion of the site created a user account that allows a questionnaire to be taken. 90% of men who began the ED questionnaire completed with a mean time of 11 minutes. 52% of men offered an appointment based on their responses completed the patient scheduling form. 71% of traffic was on mobile devices with 29% on desktop/tablet. Site use by time of day is shown in figure 1 . Mean age of patients was 53. 92% of patients had ED that occurred > 6 months. Mean SHIM score was 8.2 (IQR 4-12). 80% of participants had both desire and opportunity for sexual activity, 20% did not meet both criteria and thus SHIM scores were less valid for these men. Of the users 28% had never tried pde5s, 32% had partial success with pde5s, 24% could not tolerate or afford pde5s and 42% had unsatisfactory results with pde5s. PDE5 naïve patients were seen by an internal medicine MD specializing in men's health, 10 were seen by surgeons as they requested IPPs and the rest were seen by a combination of men's health APPS and urology attendings for second line treatments and penile doppler. Interestingly, 66% of men were interested in undergoing penile doppler to better understand the etiology of their ED. Hypertension (40%) and diabetes (22%) were the most common medical comorbidities. 36% of the cohort had a strong family history of cardiac disease. Conclusions: Men with ED can be effectively triaged through a website application. Most men with pde5 refractory ED wish to pursue penile doppler. The majority of patients seen had watched educational video material ahead of time, facilitating a more sophisticated and streamlined patient interaction. Disclosure: No